FIREFIGHTING COMBAT WITH FIRE RETARDANTS AT DIFFERENT CONCENTRATIONS - Fiedler, Nilton César; Lacerda, Guilherme Rizo; Cordeiro Ramalho, Antonio Henrique; Christo Berude, Leandro; Neves, Felipe Patricio; Rodrigues, Carla Krulikowski (Floresta, 2019)
Forest fires are responsible for the destruction of millions of hectares of forest worldwide, and they lead to diverse economic, social, and landscape damage. Thus, the development of techniques to combat them has become increasingly necessary. In this context, this study aims to evaluate the efficiency of different fire retardants at different concentrations in fighting forest fires, considering the burning times and intensities of forest fuel. The study was conducted inside Eucalyptus spp. stands using three fire retardants (Silv-Ex, F-500, and HoldFire) at three concentrations (1%, 1.5%, and 2%), in addition to a water-only control. A completely randomized design was used, and the statistical analysis was completed based on experimental arrangements (factorial 3x3). Variables evaluated during the burning process were as follows: burning times (the time required for the flames to consume all forest fuel within the sample, with and without the retardant) and intensity of burning. Results regarding the time and intensity of burning in relation to the concentrations indicated a decreasing trend as the latter were increased, classifying the highest dose (2%) as the most efficient. For the retardants, all were observed to be efficient, with Silv-Ex being the most appropriate as it significantly reduced the burning intensity and increased the burning time of the forest fuel.